2016
DOI: 10.4018/ijmbl.2016010103
|View full text |Cite
|
Sign up to set email alerts
|

Fostering Collaborative Learning with Mobile Web 2.0 in Semi-Formal Settings

Abstract: Mobile Web 2.0 technologies such as: mobile apps, social networking sites and video sharing sites have become essential drivers for shaping daily activities and meeting learning needs in various settings. However, very few studies link mobile Web 2.0 to supporting collaborative learning in real-life problem solving activities in semi-formal contexts. A study of collaborative learning and mobile Web 2.0 usage practices in real-life problem solving activities was carried out with 18 participants recruited from a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 25 publications
1
1
0
Order By: Relevance
“…These results are in line with the results of research of Mirmoghtadaie, Ahmady (2019), Najafi (2017), Savari and Falahi (2017), Ajam (2015), Karami and Salari (2013), Seyedi, Yaghoubi (2012), Li et al (2019). ), Colasante Hall Vanden, Elsen (2017), Mwanza-Simwami (2016), Ardid et al (2015), Glazer (2012), Khan (2007) and Akker (2003) were consistent. For example, Mirmoghtadaie, Ahmady (2019) while conducting research concluded that combined learning had 5 levels and 40 subclasses, which included student competencies, teacher competencies, technical aspects, pedagogical field and supportive environment.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…These results are in line with the results of research of Mirmoghtadaie, Ahmady (2019), Najafi (2017), Savari and Falahi (2017), Ajam (2015), Karami and Salari (2013), Seyedi, Yaghoubi (2012), Li et al (2019). ), Colasante Hall Vanden, Elsen (2017), Mwanza-Simwami (2016), Ardid et al (2015), Glazer (2012), Khan (2007) and Akker (2003) were consistent. For example, Mirmoghtadaie, Ahmady (2019) while conducting research concluded that combined learning had 5 levels and 40 subclasses, which included student competencies, teacher competencies, technical aspects, pedagogical field and supportive environment.…”
Section: Discussionsupporting
confidence: 87%
“…In another study, Colasante and Hall Vanden Elsen (2017) designed a hybrid learning model in technical and vocational education that included three elements of active learning, interactive learning, and online communication, with a strong emphasis on faculty presence. The results of Mwanza-Simwami (2016) showed that the combined approach is more effective than traditional and electronic approaches alone. Ardid et al (2015) introduced the dimensions of combined learning including pedagogy, technology, learning style and methodology.…”
Section: Introductionmentioning
confidence: 99%